Diagnostics of Damages in Reinforced Concrete by the Parameters of Electric Response to Mechanical Impact; IOP Conference Series: Materials Science and Engineering; Vol. 471 : World Multidisciplinary Civil Engineering, Architecture, Urban Planning Symposium (WMCAUS 2018) - Petrov M. V. Maksim Vyacheslavovich; Osipov K. Yu. Konstantin Yuryevich; Fursa T. V. Tatyana Viktorovna; Dann D. D. Denis Dmitrievich (2019, 2019)
Title screen